2018
DOI: 10.3389/fnhum.2018.00174
|View full text |Cite
|
Sign up to set email alerts
|

Can Tai Chi and Qigong Postures Shape Our Mood? Toward an Embodied Cognition Framework for Mind-Body Research

Abstract: Dynamic and static body postures are a defining characteristic of mind-body practices such as Tai Chi and Qigong (TCQ). A growing body of evidence supports the hypothesis that TCQ may be beneficial for psychological health, including management and prevention of depression and anxiety. Although a variety of causal factors have been identified as potential mediators of such health benefits, physical posture, despite its visible prominence, has been largely overlooked. We hypothesize that body posture while stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 156 publications
(220 reference statements)
1
34
0
1
Order By: Relevance
“…Tai Chi and Qigong were grouped together. They were considered equivalent interventions, following other recent reviews [ 9 , 40 ], and because they are closely related having their origin in the martial art of China [ 29 ]. The other subgroup consisted of Yoga and Pilates underlying lots of similarities [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tai Chi and Qigong were grouped together. They were considered equivalent interventions, following other recent reviews [ 9 , 40 ], and because they are closely related having their origin in the martial art of China [ 29 ]. The other subgroup consisted of Yoga and Pilates underlying lots of similarities [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Authors have revealed that: − Found brain activation patterns result from different attentional focusing styles and breathing techniques performed during the investigated Health Qigong techniques [10]; − Dynamic and static body postures are a defining characteristic of mind-body practices such as Tai Chi and Qigong (TCQ). A growing body of evidence supports the hypothesis that TCQ may be beneficial for psychological health, including management and prevention of depression and anxiety [11]; − Baduanjin, a Chinese traditional Qigong exercise that focuses on a mind-body integration, is considered to be an effective exercise in promoting health [12]; − Mindfulness-based Baduanjin exercise may be effective for alleviating musculoskeletal pain and improving overall sleep quality in people with chronic illness [13].…”
Section: Introductionmentioning
confidence: 99%
“…The smooth movements in Qigong are synchronized with this calm breathing, for instance, inhaling while slowly raising the arms and exhaling when the arms are slowly lowering [ 47 ]. This component of Qigong is related to medical breathing interventions aimed at improving health complaints such as high blood pressure and anxiety [ 56 , 57 , 58 , 59 ].…”
Section: The Role Of Qigong For Recovery and Healthmentioning
confidence: 99%
“…In recent decades, scientific research into Qigong has increased as researchers have become increasingly aware of Qigong as a possible intervention for different ailments, such as hypertension, anxiety, and depression (e.g., [ 59 , 60 , 61 , 62 ]). Most studies reported below are Randomized Controlled Trials, whereby participants are randomly assigned to either the Qigong intervention group or a control group.…”
Section: The Role Of Qigong For Recovery and Healthmentioning
confidence: 99%